A new beginning of trauma theory in literature - Azmi, M.N.L. (2018)
Cathy Caruth's Unclaimed Experience: Trauma, Narrative, and History and Kali Tal's Worlds of Hurt: Reading the Literatures of Trauma sparked a great attention to literature lovers. Her suggestion on Trauma Theory enlightens a new era in poststructral approach of analyzing literary texts. Slowly but gradually, several models were introduced which inherent neurobiological features of trauma that refuse representation and cause dissociation were significant to arguments that sought to emphasize the extent of profound suffering from an external source, whether that source is an individual perpetrator or collective social practice. It was quickly accompanied by alternative models and methodologies that revised this foundational claim to suggest determinate value exists in traumatic experience. However, the researcher would like to explore and reintroduce Trauma Theory in more contemporary approach so that it will be acceptable and practical in all genres of literature. Similarly, this study is in line with the critics such as Leys and Cvetkovich who establish a psychological framework apart from the classic model thus produce different conclusions regarding trauma's influence upon language, perception, and society. The researcher believes that Trauma Theory should be viewed in a larger conceptual framework rather than the social psychology theories in addition to neurobiological theories; that is in the view of Critical Thinking. This stance might therefore consider dubious the assertion of trauma's intrinsic dissociation. The discussion focuses more on the roles of Critical Thinking in supporting Trauma Theory in several selected poems. In conclusion, the findings might prove that Critical Thinking and Trauma Theory can be blended together in developing learners' intellectuality and maturity in analyzing and appreciating literary texts.